ALIH INOVASI CASSAVA FLOUR SEBAGAI PEMANFAATAN SISA PARUTAN SINGKONG KERIPIK KACA AKOPA - Marta, Rustono Farady; Nurhayati, Nurhayati; Dwijayanti, Risqi Inayah; Agustinus, Ferdinand; Luahambowo, Melkisedek (Community Services and Social Work Bulletin, 2022)
One of the most abundant high-carbohydrate foodstuffs in Indonesia is cassava, this is what Keripik Kaca (Glass Chips) AKOPA uses as a MSME Partner which is the target of Community Service activities from Universitas Satya Negara Indonesia. The main objective of this community service activity is based on optimizing Keripik Kaca AKOPA’s waste to be used as cassava flour or tapioca flour. The methods used include training and mentoring as well as evaluation of activities to ensure the quality of the services presented. Based on the results of community service, a cassava-based derivative innovation transfer product was obtained, namely Cassava Flour. The product will be marketed through various online channels. This is done in order to increase the usability value as well as the selling value of cassava-derived products.